Comparación jurídica desde el sur global genealogía de un proyecto crítico - Merino Acuña, Roger (2018)
Comparative Law is considered a discipline inside the study of Law, characterized by contrasting the legal regulations and the legal development of the different legal systems around the world, under the same premises. In addition, Critical Comparative Law does deeper analysis on the development of legal systems according to their context, letting be a superficial comparison, as in the case of the Global South.In this article, the author analyzes several theoretical bases of Comparative Law, as well as the main questions of orthodox and heterodox theories related to the text. Especially the role of the Global South academy in this discipline.